2021
DOI: 10.1073/pnas.2111938119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of methanediol [CH 2 (OH) 2 ]: The simplest geminal diol

Abstract: Geminal diols—organic molecules carrying two hydroxyl groups at the same carbon atom—have been recognized as key reactive intermediates by the physical (organic) chemistry and atmospheric science communities as fundamental transients in the aerosol cycle and in the atmospheric ozonolysis reaction sequence. Anticipating short lifetimes and their tendency to fragment to water plus the aldehyde or ketone, free geminal diols represent one of the most elusive classes of organic reactive intermediates. Here, we affo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…22 CH 2 (OH) 2 can also be generated via energetic processing of low-temperature methanol–oxygen ices and characterized with mass spectrometry. 23 In this work, gaseous CH 2 (OH) 2 was simply generated via the volatilization of a 10% (w/w) aqueous formaldehyde solution, which was prepared by dissolving paraformaldehyde in pure water under reflux at 85 °C for 300 minutes and filtering it through a 0.22 μm syringe filter. The infrared spectrum of the vapour from the methanediol solution is shown in Fig.…”
mentioning
confidence: 99%
“…22 CH 2 (OH) 2 can also be generated via energetic processing of low-temperature methanol–oxygen ices and characterized with mass spectrometry. 23 In this work, gaseous CH 2 (OH) 2 was simply generated via the volatilization of a 10% (w/w) aqueous formaldehyde solution, which was prepared by dissolving paraformaldehyde in pure water under reflux at 85 °C for 300 minutes and filtering it through a 0.22 μm syringe filter. The infrared spectrum of the vapour from the methanediol solution is shown in Fig.…”
mentioning
confidence: 99%
“…The spectra of the unprocessed ices revealed prominent absorptions (Fig. 5a and Table 3) of methanol such as the broad O–H stretching mode (3020–3600 cm −1 ; v 1 ), C–H stretching fundamental (2993 cm −1 ; v 2 ), the symmetric stretching modes of the methyl group (2956 cm −1 , v 9 ; 2828 cm −1 , v 3 ), the C–H bending mode (1455 cm −1 ; v 5 ), and the C–O stretching mode (1030 cm −1 ; v 8 ); 42,45,46 intense absorptions of acetaldehyde such as the overtone mode (2865 cm −1 ; 2 v 6 ), stretching mode of the carbonyl moiety (1718 cm −1 ; v 4 ), and γ r (CH 3 ) (1123 cm −1 ; 2 v 8 ) 16,47 are also prominent.…”
Section: Resultsmentioning
confidence: 99%
“…2a and Table S1, ESI†)), we pursue the following strategy to investigate their formation in methanol–acetaldehyde ices. Upon interaction with energetic electrons, the methanol (CH 3 OH) molecule can decompose via atomic hydrogen loss to the hydroxymethyl radical (ĊH 2 OH, A ) and methoxy radical (CH 3 Ȯ, B ); 40,43,44,46 likewise, the acetaldehyde (CH 3 CHO) molecule can decompose via atomic hydrogen loss to the acetyl radical (CH 3 ĊO, C ) 36 and – in principle – to the vinoxy radical (ĊH 2 CHO, D ). Species A–D correspond to radicals containing distinct functional groups which are incorporated into products by recombination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al then reported successful synthesis and detection of gaseous methanediol in 2021. 25 Gaseous methanediol is prepared by exposing methanol-oxygen ices to high energy electrons followed by sublimation. Analysis with photoionization-reflectron time-of-flight mass spectrometry subsequently identifies the species together with IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%